Geese not susceptible to virulent subgroup J avian leukosis virus isolated from chickens. Issue 1 (2nd January 2020) - Mu, Xiaohui; Xu, Moru; Zhu, Shanyuan; Xiao, Wenhua; Shen, Xi; Qin, Aijian
ABSTRACT: To determine whether geese are susceptible to infection by avian leukosis virus (ALV), 702 serum samples from domestic and foreign goose breeds were screened for p27 antigen as well as being inoculated into DF-1 cell cultures to isolate ALV. Although 5.7% of samples were positive for p27 antigen, reactivity appeared to be non-specific because no ALV was detected in the corresponding DF-1 cultures. To further determine whether geese are susceptible to ALV-J isolated from chickens, ALV-J strain JS09GY7 was artificially inoculated into 10-day-old goose embryos, with one-day-old hatched goslings then screened for p27 antigen and the presence of ALV. In all cases, the results of both tests were negative. Liver tissues from the 1-day-old goslings were screened using a polymerase chain reaction-based assay, which failed to amplify ALV-J gene fragments from any of the samples. Further, no histopathological damage was observed in the liver tissues. ALV-J was further inoculated intraperitoneally into one-day-old goslings, with cloacal swabs samples and plasma samples then collected every 5 days for 30 days. All samples were again negative for the presence of p27 antigen and ALV, and liver tissues from the challenged geese showed no histopathological damage and were negative for the presence of ALV-J gene fragments. Furthermore, p27 antigen detection, PCR-based screening, and indirect immunofluorescence assays were all negative following the infection of goose embryo fibroblasts with ALV-J. Together, these results confirm that virulent chicken-derived ALV-J strains cannot infect geese, and that p27 antigen detection in goose serum is susceptible to non-specific interference.